THE EFFECT OF SOCIAL SUPPORT BASED ON SHORT MESSAGE SERVICE (SMS) ON COMPLIANCE IN TREATMENT AND REDUCTION OF BLOOD PRESSURE IN HYPERTENSION PATIENTS IN BETUN PUSKESMAS AND BESIKAMA PUSKESMAS - Nursalam Nursalam; Lingga Curnia Dewi; Ester Widhiastuti (Universitas Airlangga, 2020)
Background: Hypertension is a chronic disease that causes morbidity and mortality in cardiovascular disease and affects more than 1 billion people worldwide. Non-adherence to hypertension therapy is a factor that inhibits blood pressure control so that it requires interventions to improve therapy adherence, which is caused by various factors one of which is social support. This study aims to analyze the effect of SMS-based social support on adherence to treatment and blood pressure reduction in hypertensive patients. Method: Quasi-experimental research design with pre-post test control group design involving 30 treatment groups and 30 control groups, sampling technique: purposive sampling. The independent variable of this study is social support based on Short Message Service (SMS) while the dependent variable is adherence to treatment and decreased blood pressure in hypertensive patients. Data obtained using a questionnaire and observation, then analyzed using the Wilcoxon Signed Rank Test and Mann Whitney with a degree of significance α≤ 0.05. Results: SMS-based social support significantly affected treatment adherence (p = 0,000), and decreased blood pressure (p = 0,000). Discussion: SMS-based social support has positive benefits for improving adherence to treatment and reducing blood pressure in hypertensive patients, for future studies, researchers suggest that interventions are given routinely to have a better impact.Keywords: influence of social support, short message service, adherence to medication, blood pressure, hypertension